Lessons learned during the process of reporting individual genomic results to participants of a population-based biobank - Leitsalu, Liis; Reigo, Anu; Palover, Marili; Nikopensius, Tiit; Läll, Kristi; Krebs, Kristi; Reisberg, Sulev; Mägi, Reedik; Kals, Mart; Alavere, Helene; Nõukas, Margit; Kolk, Anneli; et al. (European journal of human genetics : EJHG, 2023)
The return of individual genomic results (ROR) to research participants is still in its early phase, and insight on how individuals respond to ROR is scarce. Studies contributing to the evidence base for best practices are crucial before these can be established. Here, we describe a ROR procedure conducted at a population-based biobank, followed by surveying the responses of almost 3000 participants to a range of results, and discuss lessons learned from the process, with the aim of facilitating large-scale expansion. Overall, participants perceived the information that they received with counseling as valuable, even when the reporting of high risks initially caused worry. The face-to-face delivery of results limited the number of participants who received results. Although the participants highly valued this type of communication, additional means of communication need to be considered to improve the feasibility of large-scale ROR. The feedback collected sheds light on the value judgements of the participants and on potential responses to the receipt of genetic risk information. Biobanks in other countries are planning or conducting similar projects, and the sharing of lessons learned may provide valuable insight and aid such endeavors.